PERFORMANCE OF FAMILY PLANNING INSTRUCTORS IN REDUCING BIRTH RATES AT THE SUKABUMI REGENCY POPULATION CONTROL AND FAMILY PLANNING SERVICE - Dwinta Artha Bella; Andi Mulyadi; Dine Meigawati (DIA: Jurnal Administrasi Publik, 2025)
This research aims to determine and explain the performance of Family Planning Instructors at the Sukabumi Regency Population Control and Family Planning Service to reduce the birth rate. Qualitative descriptive methods, such as interviews, observations, and documents, were used in this research. Then, the unit of analysis is the Family Planning Counselor at the Sukabumi Regency Population Control Service, who has responsibility for implementing the family planning program. Using snowball sampling techniques, researchers will use two types of informants, namely key informants and supporting informants. Data collection techniques in this research were carried out through observation, interviews, documentation, and audio and visual media. In validation, researchers examine the entire process, from data collection, analysis, and interpretation to conclusion. To validate research data, researchers will use triangulation techniques. Based on the research results, it can be concluded that the quality of work of Family Planning Counselors in the last year was quite good and satisfactory. Punctuality, which prioritizes completing work on time with minimal errors, is implemented in implementing the Family Planning (K.B.) program in the field. Initiatives that emphasize independence, creativity, courage to take risks, and responsibility are implemented by family planning instructors. Communication, which includes the use of appropriate media, good communication skills, is critical factors in efforts to reduce birth rates through the family planning program in Sukabumi Regency.